Social problems of senior citizens as a subject area of scientiﬁc research - E. M. Kueva (Вестник Майкопского государственного технологического университета, 2024)
In the context of rapid social, economic and technological changes, the relevance of research into the social problems of the elderly is increasing, as they face numerous challenges that require deep scientiﬁc understanding and the development of adequate solutions. The main goal of the research is to analyze and systematize social problems faced by the elderly, as well as to determine the most effective approaches to solving them. To achieve this goal, an integrated approach was used, including analysis of scientiﬁc literature, classiﬁcation of approaches and formulation of practical recommendations. As a result, key areas of research were deﬁned, main trends and strategies for solving the problems of the elderly population were identiﬁed. The article examines ﬁve research approaches: a biological-sociological one, which connects the physiological and social aspects of aging; a social-dynamic one, emphasizing the inﬂuence of changing social conditions; an integration-digital one, studying the impact of technology on the lives of the elderly; a social-status one, considering the relationship between social status and quality of life; and active-adaptive one, emphasizing the active participation and adaptation of the elderly in society. These approaches present diverse perspectives and strategies for improving the lives of senior citizens. The study highlights the need for regularly updating scientiﬁc data and methods to develop effective programs and policies that help improve the quality of life of the elderly and their active participation in public life.